The Effect of Models Creative Problem Solving and Problem Based Learning to Improvability Problem Solving Students - Yenita Sesriani (JMEA : Journal of Mathematics Education and Application, 2022)
A preliminary study shows that the ability of problem students is still low. The results of the preliminary test show that 50% of students get a bad category. The application of the model's CPS and PBL is an alternative solution to be able to improve it. This research is an experimental study to look at the different effects of the application of CPS and PBL on increasing the abilities Problem-Solving students. The research data was obtained through the ability to test Problem Solving before and after the action. Referring to the results of the descriptive analysis, the average score of students' problem-solving abilities in learning CPS increased by 40.29 points. In learning PBL increased by 38.77 points. It can be concluded that the application of the two models can improve the abilities problem-solving of students'. And there are differences in increasing skills problem solving between students with the application model CPS and students who learn with the model PBL. The learning model CPS is higher with an n-gain value of 0.80 than students who receive learning PBL with an n-gain value of 0.66.